Need analysis on Spoken Language Topics for English for Hotel and Tourism Course at English Department of Universitas Negeri Padang - Suci Nazira; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2023)
This research aimed to analyze spoken language topics needed and spoken utterances used by people in hotel industry for English for Hotel and Tourism course at English Department of Universitas Negeri Padang. They were analyzed based on target situation in hotel industry namely, asking and giving information, handling complaints, asking for service, and handling service by phone. This research used a descriptive qualitative research. This research chose 44 front office department staffs, 42 housekeeping department staffs, and 49 food and beverage department staffs from 4 and 5 star hotels in Padang as the sample. The hotel staffs are from The Zhm Premiere Hotel, Santika Premiere Hotel, Truntum Hotel, Mercure Hotel, and Mercure Hotel. The data were obtained through questionnaire and interview. As the result of questionnaire, this research found 34 spoken language topics needed by front office department staffs. 22 topics were needed by housekeeping department staffs. Then, 30 topics were needed by food and beverage department staffs based on target situation. Furthermore, as the result of interview, this research found 493 variations of spoken utterances used by people in hotel and tourism industry of spoken language topics needed based on target situation. It is suggested to the lecturers of English for Hotel and Tourism course to develop the teaching materials of spoken language topics needed and spoken utterances used by people in hotel industry that is line with the current needs so that students can work effectively in this industry.